Evaluation of the structured bowel management program in inpatient rehabilitation: a prospective study. Issue 6 (12th March 2016) - Amatya, Bhasker; Elmalik, Alaedin; Lowe, Matthew; Khan, Fary
Abstract: Purpose : The purpose of this study is to evaluate the impact of the structured bowel management program (SBMP) in an inpatient rehabilitation service. Method : Prospective recruitment of consecutive patients admitted to the rehabilitation unit ( n = 100). Each patient was assessed for bowel dysfunction on admission and an individualised SBMP was instituted based on the clinical needs. The assessments were at baseline (T1), and discharge from ward (T2) using validated questionnaires. Program evaluation was at 3-month (T3) post-discharge. Results : Participants were predominantly female (52%), mean age 68 ± 13 years. Almost one-half (43%) had neurological conditions and 41% musculoskeletal problems. At admission, 62% self-reported bowel dysfunction, mainly constipation (82%) and faecal incontinence (FI) (11%). At T2, participants showed significant improvement in bowel habit and stool consistency (Bristol stool chart, p < 0.001); severity of bowel symptoms such as FI (Wexner FI score, p < 0.05); and impact on quality of life (FI Quality of Life (QoL) subscales: "life style" and "coping/behaviour", p < 0.05 for both). All functional independent measure "motor" and "cognition" subscales improved significantly ( p < 0.01 for all), with moderate to large effect sizes ( r = 0.5–0.7). No adverse effects were reported. Conclusions : Bowel management should be a priority within rehabilitative services. Evidence-based SBMP can improve bowel symptoms and enhance overall QoL in patients admitted to rehabilitation settings. Implications for Rehabilitation: Bowel dysfunction is common in inpatient rehabilitation settings. A structured bowel management program can improve bowel symptoms and enhance overall QoL in patient. Bowel management should be a priority for patients admitted to rehabilitation settings.